Glucuronidation and UGT isozymes in bladder: new targets for the treatment of uroepithelial carcinomas? - Sundararaghavan, Vikram L. (Oncotarget, 2016)
Bladder cancer has been linked to numerous toxins which can be concentrated in the bladder after being absorbed into the blood and filtered by the kidneys. Excessive carcinogenic load to the bladder urothelium may result in the development of cancer. However, enzymes within the bladder can metabolize carcinogens into substrates that are safer. Importantly, these proteins, namely the UGTs (uridine 5-diphospho-glucuronosyltransferases), have been shown to possibly prevent bladder cancer. Also, studies have shown that the UGT1 expression is decreased in uroepithelial carcinomas, which may allow for the accumulation of carcinogens in the bladder. In this review, we discuss the UGT system and its protective role against bladder cancer, UGT genetic mutations that modulate risk from chemicals and environmental toxins, as well as targeting of the UGT enzymes by nuclear receptors.